A full review of online OPAT educational resources for patients and healthcare professionals in the grey literature revealing resource gaps - C Watson; J Spencer-Jones; K Heard; A Jenkins; T P Gauthier; B A Rogers; A N Marizan Nor; F B Sime; M Gilchrist (JAC-Antimicrobial Resistance, 2026)
Abstract Background There is an absence of practical educational resources for both healthcare professionals and patients, which are crucial to support safe and consistent delivery of Outpatient Parenteral Antimicrobial Therapy (OPAT) across health systems. Objectives To identify and appraise high-quality, free-to-access educational resources available in the English language across grey literature to support OPAT service delivery for healthcare professionals and/or patients. Methods This review searched three grey-literature databases, conducted a targeted web search, reviewed six organizational websites and consulted international experts in OPAT service delivery to identify free-to-access educational resources published in the English language to address the educational needs of healthcare professionals and patients. Study investigators identified a final list of resources based on applied inclusion and exclusion criteria and categorized as peer-reviewed accredited, non-accredited or expert-opinion-based materials. Results A total of 36 potential resources were identified, of which nine were selected for review. Resources were grouped into four categories; webinars and conference archives, expert-led service overviews, patient-facing information and online courses for healthcare professionals. Only two patient-directed OPAT educational materials were identified and these were based on expert opinion rather than formally accredited materials. Most resources were developed within high-income healthcare systems but offer adaptable principles that can support OPAT practice development in low- and middle-income country settings. Conclusions The lack of readily available resources aimed at general OPAT information represents a missed opportunity in patient care and education. Addressing these educational gaps is essential to support safe, effective and sustainable OPAT service delivery and improve patient outcomes.